Homeschooling - Kaufeld, Jenny (--For dummies., 2020)
"Interest in homeschooling was booming even before the coronavirus pandemic inspired many parents to consider the homeschooling choice as an alternative to in-person classroom learning. Fully updated with new resources and technologies, this guide is just what you need to help you decide whether homeschooling is right for your family. Learn about the rewards and challenges presented by homeschooling, how to ensure that your children receive a well-rounded education, where to find tools that help you develop appropriate curricula, and how to connect with the homeschooling community." --